Permeability and dynamic elastic moduli of controlled porosity ultra-precision aerostatic structures - Durazo-Cardenas, Isidro; Corbett, John; Stephenson, David J. (Elsevier Science B.V., Amsterdam., 2014)
Porous ceramic aerostatic bearings enable precise and smooth motion and improved stiffness compared with widely used orifice restrictor bearings. However, the processing techniques so far used are too complex or rely in lowering the sintering temperature to increase fluid flow. Preferred combinations of fine-grade alumina powders and starch granules were used to produce quality porous structures using fixed processing parameters. Component shrinkage, permeability, pore size and elastic properties were comprehensively characterised as a function of porosity. The new porous ceramic structures exhibited controllable and reproducible permeability and modulus, within the range required for ultra-precision porous aerostatic applications
Keywords: Porous ceramic aerostatic bearings